Strategic Leadership Qualities to Enhance the Payment Culture for Municipal Services within an African Context - Enwereji, Prince; Potgieter, M. (International Review of Management and Marketing, 2022)
The purpose of this study was to identify the strategic leadership qualities required of municipal role-players to cultivate a payment culture for municipal services in the North West Province in South Africa. A systematic review and comparative study were conducted to compare the strategic competencies of executives in Canada, the United States of America, and the United Kingdom. These are considered leading countries in service provision. The study proposes that municipalities should be visionary and result-driven, and engage people, while collaborating with relevant stakeholders to achieve desired results. The study further recommends that municipal role players adopt strategic leadership to achieve change through a planning and development process that involves assessing future goals and mapping specific actions. Furthermore, municipalities should achieve their goals through a strategic process of analysis, formulation, implementation, and evaluation, all of which entail a number of constituent tasks.